2017
DOI: 10.1167/iovs.16-21285
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Light-Induced Lacrimation and the Melanopsin-Driven Postillumination Pupil Response

Abstract: Citation: Lei S, Goltz HC, Chen X, Zivcevska M, Wong AMF. The relation between light-induced lacrimation and the melanopsin-driven postillumination pupil response. Invest Ophthalmol Vis Sci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…1 a). Although they represent a small fraction (∼1%–3%) of the total retinal ganglion cell population, 1 4 ipRGCs are critical for entrainment of circadian rhythm, 5 , 6 aversive responses to light, 7 light-induced lacrimation, 8 and control of pupil diameter. 9 11 Disruption of these reflexive visual functions is seen in many clinical conditions, leading to the speculation that dysfunction in the melanopsin system is responsible.…”
mentioning
confidence: 99%
“…1 a). Although they represent a small fraction (∼1%–3%) of the total retinal ganglion cell population, 1 4 ipRGCs are critical for entrainment of circadian rhythm, 5 , 6 aversive responses to light, 7 light-induced lacrimation, 8 and control of pupil diameter. 9 11 Disruption of these reflexive visual functions is seen in many clinical conditions, leading to the speculation that dysfunction in the melanopsin system is responsible.…”
mentioning
confidence: 99%
“…An objective assessment tool for photophobia is important not just for diagnosis, but also to monitor changes over time and evaluate treatment efficacy. Several efforts have been made toward the development of objective techniques using involuntary light-induced behavioral responses, such as squinting 22,33 and lacrimation, 15 as markers for photophobia. These physiologic behavioral indices, however, can be invasive, are often not closely aligned with the clinical complaint of photophobia, and may not be useful in quantifying light sensitivity for individuals with aberrant blink responses (e.g., as seen in benign essential blepharospasm) and aberrant lacrimal responses (e.g., as seen in dry eye syndrome).…”
mentioning
confidence: 99%
“…Ten participants with episodic migraine with or without aura (6 with aura, 9 females, mean age 34 ± 8.7 years, age range 22–49 years) and 11 visually normal controls (5 females, mean age 25 ± 6.6 years, age range 18–42 years) with no history of migraines or photophobia were included in this study. Control data sample has been previously published [ 29 ]. All participants with migraine fulfilled the diagnostic criteria of the International Classification of Headache Disorders III [ 31 ] and had confirmed migraine diagnosis by a licensed clinician, with no other neurologic abnormalities or history of traumatic brain injury (see Table 1 for clinical features).…”
Section: Methodsmentioning
confidence: 99%
“…We recently used simultaneous chromatic pupillometry recording and light-induced lacrimation measurement to investigate photo-sensitivity (a phenomenon closely associated with photophobia) in normal participants. We found that these two phenomena are highly correlated, and that both are mediated predominantly by melanopsin-induced ipRGC photoactivity [ 29 ]. However, photophobia and light-induced lacrimation, as well as their underlying mechanisms, have not been well-studied in patients with migraine.…”
Section: Introductionmentioning
confidence: 99%